Death and Dying in the Upanisads, Bhagavad-Gita and Caraka Samhita - Claire Hilton (Opticon1826, 2007)
Death, dying and immortality appear at the interface of medical, cultural and religious teaching in many cultures and over thousands of years. Chinese medicine advocated yangsheng (life nurturing), and the desire for immortality was documented during the Han dynasty (206 BCE – 220 CE).1 Galen (129-c216CE) wrote on both medical aspects of long life and philosophical ideas of creation and soul,2 whilst medical ethics today in western cultures not infrequently links to religious beliefs of Christianity and Judaism originating over two millennia ago. This essay explores death and dying in ancient Sanskrit religious and medical texts.
Keywords: sanskrit; immortality; dying; death